Efficacy of the cognitive functional therapy (CFT) in patients with chronic nonspecific low back pain: a study protocol for a randomized sham-controlled trial - Mariana Romano de Lira; Ney Meziat‐Filho; Gabriela Zuelli Martins Silva; Thaís Cristina Chaves (2022)
Abstract Background Chronic low back pain is a public health problem, and there is strong evidence that it is associated with a complex interaction of biopsychosocial factors. Cognitive functional therapy (CFT) is a promising new intervention that deals with potentially modifiable multidimensional aspects of pain (e.g., provocative cognitive, movement, and lifestyle behaviors). Methods To investigate the efficacy of CFT compared with a sham intervention for pain intensity and disability post-intervention (immediately after the last session) in patients with non-specific chronic low back pain (CLBP). This study is a randomized controlled trial in which 152 (18–60 years old) patients with CLBP will be enrolled. The patients will be randomly allocated to receive (1) CFT intervention or (2) sham intervention. The experimental group will receive individualized CFT in a pragmatic manner (5 to 7 sessions) based on the clinical progression of the participants. The sham group will attend six sessions: consisting of 30 min of photobiomodulation using a detuned device and more than 15 min of talking about neutral topics. Patients from both groups also will receive an educational booklet (for ethical reasons). Participants will be assessed pre and post-intervention, 3 months, and 6 months after randomization. The primary outcomes will be pain intensity and disability post-intervention. The secondary outcomes will be: pain intensity and disability at 3- and 6-month follow-up, as well as self-efficacy, global perceived effect of improvement, and functioning post-intervention, 3-, and 6-month follow-up. The patients and the assessor will be blinded to the treatment administered (active vs. sham). Statistical analysis The between-group differences (effects of treatment), as well as the treatment effect for the primary and secondary outcomes, and their respective 95% confidence intervals will be calculated by constructing linear mixed models. Discussion To the best of our knowledge, the current study will be the first to compare CFT vs. sham intervention. Sham-controlled RCTs may help to understand the influence of non-specific factors on treatment outcomes. Considering complex interventions as CFT, it is imperative to understand the impact of contextual factors on outcomes. Trial registration ClinicalTrials.gov NCT04518891 . First Posted: August 19, 2020.